Exchange Rate Shocks and Sectoral Returns Dynamics in Pre-Covid Era: An Examination through GARCH Based Dynamic Models - Javed, Hassan; Arshad Hassan (UW Journal of Management Sciences, 2023)
Purpose: The main goal of this article is to examine, using daily data from June 2000 to June 2018, the relationship between the exchange rate and sectoral returns in Pakistan. Design and Methodology: Using the ARMA GARCH model, mean and volatility Spillover are evaluated. DCC-GARCH models are also utilized to investigate the dynamic disposition of constant correlation. Findings: The study’s findings suggest that exchange rate volatility has a significant Spillover effect on industries such as those that assemble cars, cement, chemicals, commercial banks, oil and gas, and power generation and distribution, although there is little evidence to support this claim. Strong evidence is discovered against industries using the DCC-GARCH model, which is also utilized to assess the time-varying conditional correlation. Implications: The results’ implications are crucial for the advantages of portfolio diversification as well as risk management in erratic foreign exchange and stock markets. The insights of this study can be used by investors to develop investing strategies for risk control and portfolio diversification. Keywords: Mean & Volatility Transmission, Exchange Rate, Sectoral Returns, Time-varying Conditional Correlation & DCC-GARCH models.